Application of Hazard Analysis Critical Control Points (HACCP) in improving the global competitiveness of the fish industry with special reference to the Nile Perch (Tanzania) - Mlolwa, Mwanaidi Ramadhani (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhilAgric)--Stellenbosch University, 2000.